2010
DOI: 10.1111/j.1365-2311.2010.01226.x
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the timing of spring cleaning by the honeybee Apis mellifera in Poland

Abstract: 1. The honeybee Apis mellifera is of huge worldwide economic importance in the pollination of crops for human consumption. In recent years, honeybee populations have declined under pressure from diseases and pests. Climate change is increasingly being viewed as an additional threat to honeybees and yet only limited research has been carried out in this area.2. This paper reports the advance of the first cleansing flight ('spring cleaning') of the honeybee in Poznań, Poland, i.e. flights to excrete faeces, over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 19 publications
(38 reference statements)
1
23
0
Order By: Relevance
“…Field observations-The first spring activity of honeybees are cleansing flights (to excrete feces), which have been quantified by beekeepers in Poland. Comparing 25 yr of these flight records with temperature data, Sparks et al (2010) concluded the bees were starting their flights a month earlier, which over time is associated with increased temperatures occurring earlier in the season.…”
Section: Pollinator-focused Studiesmentioning
confidence: 99%
“…Field observations-The first spring activity of honeybees are cleansing flights (to excrete feces), which have been quantified by beekeepers in Poland. Comparing 25 yr of these flight records with temperature data, Sparks et al (2010) concluded the bees were starting their flights a month earlier, which over time is associated with increased temperatures occurring earlier in the season.…”
Section: Pollinator-focused Studiesmentioning
confidence: 99%
“…Under current climate change, some studies have mainly explored its potential consequences on herbivorous insects (Musolin et al 2010), whereas very little attention was focused on its direct impact on pollinators e.g., solitary bees (but see Sparks et al 2010). In contrast to the well-known social honey bee, most bee species are solitary and their offspring are largely exposed to ßuctuating ambient temperatures (Radmacher and Strohm 2011).…”
mentioning
confidence: 99%
“…Alterations in phenology are among the best-supported effects of climate change on organisms12345. So far, however, most studies focus on early-season phenology such as the earlier start of reproduction, flowering or arrival of migrant birds14678. Alterations in late-season phenology are less understood but these studies will enable better understanding of population consequences of these shifts, especially in insects16910.…”
mentioning
confidence: 99%